Psychological characteristics of the interrelationship between emotional states and decision-making styles in youth - KONONENKO, Artem (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. Numerous issues have intensified in the domestic socio-political sphere, including the challenge of individuals’ proper functioning under continuous crisis conditions. The specific ways in which emotional states influence cognitive and behavioral strategies during crisis situations remain insufficiently studied. Methods. The study employed theoretical, empirical, and psychodiagnostic methods, including the Beck Depression Inventory (A. Beck), the State-Trait Anxiety Inventory (C. Spielberger, adapted by Y. Khanin), Stress Level Diagnostic Method (R. Cattell), Decision-Making Test (DMT), Emotional Resilience Questionnaire, and mathematical-statistical data analysis techniques. Results. Findings indicate that an impulsive decision-making style positively correlates with anxiety and other negative emotions, reflecting diminished cognitive control. The rational style is associated with psycho-emotional stability and negatively correlates with depression and stress. Avoidance acts as a protective mechanism under emotional load, while the dependent style is linked to the need for social support. The intuitive style appears independent of emotional states. Emotional resilience decreases impulsivity and avoidance, emphasizing the role of self-regulation in decision-making. Significant gender differences in emotional states were identified: females exhibit higher levels of reactive anxiety and depression compared to males; they predominantly prefer the dependent decision-making style focused on others’ opinions, whereas males tend toward an impulsive style characterized by emotionality and reduced self-control. These differences are attributed to sociocultural factors and bear important implications for the development of psychological support during crises. Conclusions. The emotional state of youth during crisis periods is a key predictor of decision-making style, influenced by the intensity of emotions, sociocultural factors, and life experience. Psychological interventions should focus not only on alleviating negative emotional background but also on fostering self-regulation and rational thinking among young people.